STRUKTUR NARATIF DAN PENOKOHAN PADA NOVEL THE PERFECT CHARM KARYA DY LUNALY - Siti Nur Afifatul Hikmah; Mia Fitria (Jurnal Tarbiyatuna: Jurnal Kajian Pendidikan, Pemikiran dan Pengembangan Pendidikan Islam, 2020)
Literary work is the result of creative and imaginative human thought. Literary work is a medium that utilizes language to reveal the problems surrounding human life. Creative nature causes a person to be able to give birth to a beautiful creation. Literary work has literary value if it contains equivalence between form and content. Therefore it is worth the hand, heart and imaginative. Literary work is an expression of the author's imagination to tell various human and author issues expressing this problem through literary works such as poetry, drama, short stories and novels. The method used by researchers in the study used a qualitative descriptive method. In this study researchers tried to discuss the narrative structure and characterization of The Perfect Charm novel by Dy Lunaly. Thus this research is designed in accordance with the characteristics of qualitative research and qualitative data sources. including the following: (1) objects, (2) data, (3) data sources, (4) data collection and, (5) data analysis. Qualitative research was carried out to describe the narrative structure and characterization of Dy Lunaly's The Perfeck Charm. This research is a qualitative research. The source of the data in this research is Dy Lunaly's The Perfeck Charm with a focus on research on narrative structure and characterization. The data collection technique used is reading notes by reading and recording research subjects repeatedly until they get consistent data. The results show that: (1) the narrative structure in the novel The Perfeck Charm. The flow found in the novel The Perfeck Charm is divided into five, namely: Exposition, Complication and Conflict, Climax, Revelation, and Denousement. (2) characterizations in the novel The Perfeck Charm. The figure discussed in this study is every character in the novel The Perfeck Charm and his character. Adhela figure (Dhe) Stubborn, Not confident, Afraid, Desperate, Appreciate, Merciful, Anxious, Keep promises and Jealousy. Mama's figure is anxious, angry, and feels guilty. Alena Iri figure, and regret. Figure Julia Not desperate and fond of eating. Figure Ann Attention. Papa's attention. Ahsan Peduli figures, female idols and willing to sacrifice. Career Bri and Cheating Person. Satria Figure Handsome, Not Desperate, and Enthusiastic.